Relación entre geopolítica y comercio internacional de petróleo en Latinoamérica (2021)
Oil is a particularly important resource in the development of Latin American countries, which is why it influences the politics of nations and similarly the policies implemented by governments have a direct impact on the success or failure of the hydrocarbon industry. Just as international relations and trade have made oil linked to a geopolitical context. Thus, the first major event in the region's oil industry was the arrival of foreign multinationals that leveraged oil exports and affected resource management decisions. And over the years, several countries have implemented both nationalist and open policies impacting oil exports. However, the weak institutional sector that haunts the region is the staunch enemy of strengthening the industry.